Myocarditis and Rhabdomyolysis in a Healthy Young Man Caused by Salmonella Gastroenteritis - Warkaa Al Shamkhani; Yasmeen Ajaz; Nagham Saeed Jafar; Sunil Roy Narayanan (Case Reports in Infectious Diseases)
Salmonella gastroenteritis is a common, self-limiting, foodborne disease and a rare cause of life-threatening complications especially in immunocompetent individuals. Moreover, bacterial infections of the GI tract have been rarely reported as a cause of serious complications like acute myocarditis and rhabdomyolysis. While viral infections are commonly associated with myocarditis, bacterial infections are infrequently seen with these conditions. Similarly, bacterial infections may lead to only 5% of adult rhabdomyolysis events whereas viral-induced myositis appears to be the commonest. A 28-year-old young male with no past medical problems presented with acute salmonella gastroenteritis that was complicated by myocardial injury (most likely myocarditis), rhabdomyolysis, acute renal failure, and shock. He made an uneventful complete recovery of all complications by early recognition of these rare complications and prompt institution of appropriate therapy.